Sources of HIV information and women’s HIV knowledge in Southwest Sumba Indonesia: a cross-sectional study with mediation analysis - Angela Kurniadi; Judith A. Levy; Timothy P. Johnson (BMC Public Health)
Abstract Background Despite multiple years of government HIV educational efforts, the growing trend of new cases among women in Indonesia runs parallel with their seemingly overall lack of comprehensive knowledge about HIV. A major prevention challenge for the Indonesian government lies in delivering HIV prevention education across the world’s largest archipelago. This study investigates comprehensive HIV knowledge among reproductive-age women in Southwest Sumba, Indonesia, and the sources through which they report having learned about HIV along with potential mediators of the relationship between socioeconomic status (SES) and HIV knowledge. Methods This cross-sectional study using convenience sampling recruited 159 married women ages 15–49 years old living in 4 selected church parishes in Southwest Sumba on March 12–20, 2023. The HIV Knowledge Questionnaire-18 and items from the 2017 Indonesian Demographic and Health Survey (24 total) measured the women’s comprehensive knowledge about HIV. Additional items asked about sources through which the women had received information about HIV. One-way ANOVA examined differences in the level of HIV knowledge obtained through one or more information sources (healthcare providers, media, schools, and social network members). Mediation analysis investigated potential mediators of the relationship between SES and HIV knowledge. Results Comprehensive HIV knowledge scores ranged from 0 to 21 (mean = 10.6). About 65% of the 159 women could only correctly answer 50% or less of the questions. Most incorrect answers pertained either to Mother-to-Child HIV Transmission (MTCT) or misconceptions about the virus. One-way ANOVA revealed that the mean of HIV knowledge increased as the number of informational sources increased (p < .001). Structural Equation Modelling found that social network members, healthcare providers, and the media all had significant direct effects on HIV knowledge. In addition, an indirect positive relationship between SES and comprehensive HIV knowledge was mediated by information obtained through the media and marginally through healthcare providers. Conclusions The study’s results suggest that more extensive in-depth HIV education is greatly needed to help prevent transmission among women living in small and outlying islands in Indonesia. Wider promotion of HIV information through the media and more intensively through local healthcare providers appears a promising and likely effective means to reach these women.